Community participation in community-based tourism of Jakun Tribe, Sg. Peroh Johor - Napatah, Nurul Najwa (2020)
Indigenous communities in most countries have settled in their traditional lands since before the existence of other communities in one country. Their traditional culture is deeply embedded in their traditional lands and is closely linked to their customs and belief system. However, the process of globalization in the form of development has slowly eroded the traditional culture of the indigenous community and exposed to the threat of cultural extinction. Previous research revealed that tourism has been identified as a vital mechanism of sustainable development in rural indigenous areas. The increase in concern over the indigenous culture as an attractive tourist destination facilitates the development in indigenous peoples. Hence, community participation towards tourism is an important factor since they are the nucleus for decision making and support in the development of their place. Therefore, this research will look into the readiness and willingness of local community of Jakun Tribe Kampung Orang Asli Sg. Peroh to participate in the development of Community-Based Tourism. The effort to develop CBT in this village is a way to upgrade the current practice of tourism so that through local community participation it would increase community groups’ abilities to define, assess, analyze and act on concerns of importance to their community and village. The scoring of community readiness was conducted to obtain the stages of community awareness and readiness. By applying qualitative method of in-depth interview with the local community and selected organizations it would gain a comprehensive understanding of the level of awareness, readiness and willingness of community to participate in tourism development. The results showed that the local community are open towards more opportunity in the tourism development and ready to participate. Therefore, this study is beneficial to all tourism stakeholders in outlining strategies for tourism development in the indigenous village.